2009
DOI: 10.1158/1535-7163.targ-09-b154
|View full text |Cite
|
Sign up to set email alerts
|

Abstract B154: Thymoquinone causes mitochondrial membrane disruption and potentiates chemotherapeutic drug- and radiation-induced cytotoxicity in breast cancer cells

Abstract: Thymoquinone, which is the active constituent of the volatile oil extracted from black caraway seeds (Nigella sativa), has been reported to have antiinflammatory, antioxidant, and antineoplastic activities in vitro and in vivo. In this study we explored the mechanism by which thymoquinone inhibits breast cancer cell growth, as well as the potential of using thymoquinone in combination with conventional chemotherapeutic drugs or radiation therapy. Cytofluorimetric analysis of Oregon Green 488-stained MDA-MB-231… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This discovery agrees with previous studies on TQ. For example, the apoptotic effect of TQ on MDA-MB-231 and MDA-MB-468 breast cancer cells was reported to be induced by the mitochondrial pathway, shown by the loss of mitochondrial membrane integrity, release of cytochrome c, and cleavage of PARP [ 118 ]. Another study by El-Mahdy et al (2005) [ 62 ] reported that TQ, a p53-mediated-independent pathway, induced apoptosis in HL-60 myeloblastic leukemia, as evident by the disruption of MMP and activation of caspases, including caspase 8, 9, and 3.Pl…”
Section: Discussionmentioning
confidence: 99%
“…This discovery agrees with previous studies on TQ. For example, the apoptotic effect of TQ on MDA-MB-231 and MDA-MB-468 breast cancer cells was reported to be induced by the mitochondrial pathway, shown by the loss of mitochondrial membrane integrity, release of cytochrome c, and cleavage of PARP [ 118 ]. Another study by El-Mahdy et al (2005) [ 62 ] reported that TQ, a p53-mediated-independent pathway, induced apoptosis in HL-60 myeloblastic leukemia, as evident by the disruption of MMP and activation of caspases, including caspase 8, 9, and 3.Pl…”
Section: Discussionmentioning
confidence: 99%